The Effect Of Structural Capital And Creative Innovation On Increasing Business Performance Of The Cibaduyut Shoes Fashion Industry In Bandung City - S. Syahyono, S. Syahyono (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2019)
The creative industry has a vital role in the economic growth of development. The city of Bandung is a city that has a large proportion of the creative economy, especially in the fashion sub-sector. However, the current situation and condition of the fashion sub-sector are still challenging to achieve the expected competitive advantage. This article examines all aspects of business performance that are influenced by creative innovation and capital structure mediated. The type of research conducted in this research is descriptive-verificative survey research. The sampling technique used is probability random sampling. The study results show that creative innovation is included in the low category, and structural capital and competitive advantage are ordinary. Efforts are needed to improve performance and competitive business advantage in MSMEs in the Creative Industry Center in the Fashion Sub-sector, which can be done through synergies from creative innovation, value chains, and structural capital.